Age‐related morphometric changes of the tidemark in the ovine stifle. (20th May 2019) - Hontoir, Fanny; Pirson, Romain; Simon, Vincent; Clegg, Peter; Nisolle, Jean‐François; Kirschvink, Nathalie; Vandeweerd, Jean‐Michel E.
Abstract: Though the ovine stifle is commonly used to study osteoarthritis, there is limited information about the age‐related morphometric changes of the tidemark. The objective of this study was to document the number of tidemarks in the stifle of research sheep without clinical signs of osteoarthritis and of various ages ( n  = 80). Articular cartilage of the medial and lateral tibial condyles and of the medial and lateral femoral condyles was assessed by histology: (a) to count the number of tidemark; and (b) to assess the OARSI (Osteoarthritis Research Society International) score for structural changes of cartilage. The number of tidemarks varied between anatomical regions, respectively, from 4.2 in the medial femoral condyle to 5.0 in the lateral tibial condyle. The axial part showed a significant higher number of tidemarks than the abaxial part, for all regions except the medial tibial condyle. Whilst the tidemark count strongly correlated with age (Spearman's correlation coefficient = 0.70; 95% confidence interval (95% CI): 0.67–0.73; p  < 0.0001), the OARSI score was weakly correlated with age in our cohort of sheep (Spearman's correlation coefficient = 0.25; 95% CI: 0.19–0.30; p  < 0.0001). Interestingly, no tidemark was seen in the three animals aged 6 months. Our data indicate that the number of tidemarks increases with age and vary with anatomical region. The regional variation also revealed a higher number of tidemarks in the tibia than in the femur. This could be attributed to the local variation in cartilage response to strain and to the difference in chondrocyte biology and density.